Non-thermal plasma assisted polymer surface modification and synthesis: A review - Yanling, Cheng; Yingkuan, Wang; Chen, Paul; Deng, Shaobo; Ruan, Roger (International Journal of Agricultural and Biological Engineering, 2014)
This article reviews the applications of plasma to polymer surface modification and polymer synthesis. Plasma treatment causes changes in morphology, structure and properties of polymers. When polymers are treated using plasma, certain monomers with functional groups can be copolymerized with backbone chain or be loaded on the surface, which would help couple reaction of existing polymer chains, graft monomers onto polymers, immobilize proteins, carry antimicrobial drugs, and enhance cell attachment. Hence, non-thermal plasma process creates unique properties on polymers which allow improved and expanded applications of polymers in food packaging and biotechnology.Keywords: plasma, modification, synthesis, NTP, polymers, functional groupsDOI: 10.3965/j.ijabe.20140702.001Citation: Cheng Y L, Wang Y K, Chen P, Deng S B, Ruan R. Non-thermal plasma assisted polymer surface modification and synthesis: A review. Int J Agric & Biol Eng, 2014; 7(2): 1－9.